x → 0 lim ( 2 cos ( 2 x ) cos 4 ( 3 x ) + cos x ) tan ( x ) 1 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Your very first line already don't make sense.
e lim x → 0 ( 2 cos 2 x cos 4 3 x + cos x − 1 ) ( tan x 1 ) = e lim x → 0 ( 2 1 + 1 − 1 ) ( tan x 1 ) = e lim x → 0 ( → 2 → 1 + → 1 − 1 ) ( tan x 1 )
You did it wrong.
Log in to reply
Yes you are right. Further simplification of the first bracket in you comment tends to zero. So what's wrong with my solution?
Log in to reply
Correct and complete your solution.
Log in to reply
@Abhishek Sharma – Actually the steps you mentioned are too obvious and don't need to be necessarily mentioned. :)
Log in to reply
@Rohit Ner – So what is the point of writing the solution?
Log in to reply
@Abhishek Sharma – My solution just intends to give a idea of the approach. You can post yours if you find mine not up to the mark.
Nice solution rohit.Absolutely perfect.
pls explain the 1st line . how that -1 came ? i want to knw more about limits . plzz help me
Put x=0 →cos0=1 , (cos3×0)^4=1 ,cos2×0=1 and in 1/tanx would be tending to infinity. We know that (1)^→infinity =1. Hence Ans =1.
Your answer is wrong. 1 ∞ is an indeterminate form.
You got that answer by luck. 1 ∞ is indeterminate form.
Log in to reply
Absolute 1^tending toinfinity is not an indeterminate form.Infact tending to 1^ tending to infinity is an indeterminate form
Log in to reply
Kushal kindly revisit the indeterminate forms before replying.The following are indeterminate forms:- 1)→0/→0 2)→infinity/→infinity 3)→infinity-→infinity 4)→infinity ×→0 5)(→1)^→infinity 6)(→0)^→0 7)(→infinity)^→0 And except them no other indeterminate form exists.
Problem Loading...
Note Loading...
Set Loading...
x → 0 lim ( 2 cos 2 x cos 4 3 x + cos x ) tan x 1 = e x → 0 lim ( 2 cos 2 x cos 4 3 x + cos x − 1 ) ( tan x 1 ) = e x → 0 lim ( 2 1 + 1 − 1 ) ( tan x 1 ) = e x → 0 lim ( tan x 0 ) = e 0 = 1